Propeller Flaps - Nikhil Panse; Ankur Karanjkar (Indian Journal of Plastic Surgery)
A propeller flap is an islanded flap that reaches the recipient site through an axial rotation around its vascular axis. The degree of rotation varies from 90 degrees to 180 degrees. It is a highly reliable local reconstructive option. These flaps are simple, single-stage, easy to harvest, and not constrained by routine length-to-width ratios. Since their introduction, the technique has continued to evolve and more applications for the use of propeller flaps are being explored. In spite of their growing use in clinical practice in recent years, many reconstructive surgeons are unaware of their versatility, unsure of their safety, and apprehensive about using propeller flaps confidently. This article aims at understanding the nomenclature, key principles, biogeometry and planning, operative technical details, applications, and complications of propeller flaps.